Lingual Artery Pseudoaneurysm after Severe Facial Trauma. Issue 3 (September 2018) - Margallo, Leyre; de Zárate, Estibaliz Ortiz; Franco, Maria; Garcia-Iruretagoyena, Maria; Cherro, Rosa; Barbier, Luis; Mendiola, Josu; Constantinescu, Thomas
The mortality associated with high-energy trauma has several time peaks and variable prognosis. In the particular case of isolated head and neck trauma, management initially includes stabilizing the patient, especially the airway and circulation, and then proceeding to treat injured structures with debridement and often fracture fixation and coverage. We present a case of a male patient who suffered a severe facial trauma at his workplace. He underwent an initial uneventful emergency surgery for control of bleeding and mandibular osteosynthesis. At 2 weeks postoperatively, a second emergency surgery was required to treat a previously undiagnosed lingual pseudoaneurysm that ruptured spontaneously, with massive oral bleeding. The case highlights the clinical significance and timing of pseudoaneurysm formation, and the surveillance and high index of suspicion required for potentially life-threatening bleeding at later time peaks. Diagnostic and therapeutic angiography effectively treated the late complication. Multidisciplinary management options are reviewed, emphasizing the need for rapid decision making and collaboration to improve outcomes in such significant surgical trauma patients.